Predictors of Academic Performance of Public Elementary School Learners - Aguirre, Provilyn M.; Legaspi, Carlos Eduardo I. (Philippine Social Science Journal, 2020)
Academic performance determines the quality and standard of efficiency and effectiveness of an educational system. The Research Forum Presentation Philippines’ Approach to Assessment of the 21st Century Skills Assessment Curriculum and Technology Research Center (ACTRC) stressed that learners need to acquire 21st-century skills. To address this concern, the Philippines, through its educational agencies, including the Department of Education (DepEd) for the elementary school learners, has merged the learning approach in developing the 21st-century skills through the K to12 education reform agenda. Through its Bureau of Educational Assessment, DepEd has worked to define the skills and determine the opportunities of public elementary school learners of Bacolod City during the School Year 2019-2020. Likewise, it explores the relationship between the predictors of learners’ academic performance using the demographic, such as age, sex, birth order, family living condition, monthly family income, nutritional status, and the level of academic performance of the learners in a public elementary school.